(3OhQ GdeYde aj GdJYGWj eY eTcdI GdJCNQ GdOQGSj aj eQMdI GdJYdje GdCSGSj GdMdbI GdKGfjI aj GdVGMjI GdLfhHjIs - (3egOj, RjfH YUGes ((3HjQhJs (3GdLGeYI GddHfGfjI (B- (3GdeYgO GdYGdj ddOcJhQGg aj GdBOGH hGdYdhe GdEfSGfjI GdELJeGYjIs, 2010)
(3JgOa GdOQGSI Edi EHQGR OhQ GdeYde aj JYGWjg eY eTcdI GdJCNQ GdOQGSj aj eQMdI GdJYdje GdCSGSj heYQaI GdOhQ GdaYGd dTNUjI GdeYde aj Md gPg GdeTcdI, cPdc EjVGM OhQ GdeQGcR GdeNJUI GdeSGYOI dgPg GdMGdGJ, heOi NOeJgG ddJdGejP(B. (3EYJeOJ GdOQGSI GdefgL GdhUaj(B- (3GdJMdjdj, MjK QUOJ MQcI SJ eOGQS aj GdVGMjI GdLfhHjI dHjQhJ (B((3GKfJGf efgG NGUI, GKfJGf QSejI, hGKfJGf THg eLGfjI(B)(3, hTedJ GdYjfI (B120 (3JdejkPG eJCNkQG OQGSjG aj GdMdbI GdKGfjI ef GdJYdje GdCSGSj Vef gPg GdeOGQS h (B120 (3CSJGPG(B. (3ceG hCLQjJ ebGHdGJ eY GdeQTOjf GdJQHhjjf deOGQS GdYjfI hHYV GdeQTOjf aj GdeQGcR GdJYdjejI GdJj JYfi HGdOYe GdeOQSj ddJdGejP GdPjf jYGfhf ef eTcdI GdJCNQ GdOQGSj(B. (3hGSJNOeJ HGdEVGaI Edi GdebGHdI JbfjI GdESJeGQI dLeY GdeYdheGJ(B. (3HjfJ GdfJGFL Cf GdeYde ojcSH GdJdGejP GdeaGgje hGdeYGQa GdYdejI, hgh hSjdI dJfejI GdLGfH GdeYQaj hGdPgfj YfOge, ceG Cfg jSGYO GdJdGejP Ydi GLJjGR GdUYhHGJ GdJj JYjb JbOeg YdejkG hELJeGYjkG, ef NdGd JTNjUg deTcdI GdJCNQ GdOQGSj, hcjajI GdhbGjI efgG heYGdLJgG HGdJYGhf eY GdCgd hGdEOGQI hGdeQTO GdJQHhj(B. (3Jbhe GdeQGcR GdJYdjejI HOhQ ege heSGYO ddeOQSI hGdCgd fJjLI fbU aj NHQGJ HYV GdeOGQS Ch YOe JhGaQ eQTO JQHhj ajgG, hgPg GdeQGcR JaJbO GdOYe GdeGdj dJbOje GdGSJaGOI hGdeSGYOI dCcHQ YOO eecf aj GdeLJeY(B. (3ceG hHQR HYV ef gPg GdeQGcR GdJj JHZj GdQHM GdeGOj abW(B.s
(3GdfhY (B: (3QSGdIs
Keywords: Banlieu du Sud; Cycle primaire; Elementary Education; Les Attitudes et conceptions des enseignants; Retardation scolaire; South of Beirut; Students retardation; Teachers attitudes and conceptions; (3GdJCNQ GdOQGSjs; (3GdVGMjI GdLfhHjIs; (3GdeQMdI GdGHJOGFjIs; (3ehGba GdeYdejf hJUhQGJges